A Study On The Genetic Diversity Analysis Of A Medicinally Potential Herb- Enicostemma Littorale Blume (Gentianaceae) - P.T.V.LAKSHMI; A. ANNAMALAI; C. RAMYA (International Journal of Pharma and Bio Sciences, 2011)
Enicostemma littorale Blume of Gentianaceae, thriving in many parts of India, South America and some parts of Africa, serves as an important drug for various therapeutics and has been in use traditionally for many diseases. Although, it is identified as an important medicinal plant there seems to be no information on the extent and nature of genetic diversity analysis at the molecular level. Therefore the genetic diversity was analysed using RAPD markers for populations collected from three different regions across Tamil Nadu. Two random decamer primers generated a total of 43 amplified products. The most fragment number amplified by one primer was 26 out of which 7 accounting to 27% were polymorphic in nature. From the RAPD data, an UPGMA dendrogram illustrating the genetic relationship has been computed and the samples were divided into two clusters based on the genetic distance between the samples. The highest and lowest relatedness observed among the samples were based on the distance matrixes which were detected as 0.20 and 0.58, respectively. This relatedness seemed to depend on the nearby location and environmental condition.